Kurikulum Merdeka Belajar Kampus Merdeka untuk Memenuhi Kebutuhan Pembelajaran Abad 21 - Muhamad Frananda; Maya Dewi Kurnia; Jaja Jaja; Cahyo Hasanudin (Jurnal Pendidikan Edutama, 2023)
Abstract: Learning is an effort to equip students with materials to support learning activities in the classroom. To improve learning, this research aims to make the existence of an independent curriculum for learning in an independent campus is to meet the needs of learning in the 21st century. The method used in this research is library research, which is conducted by analyzing data sources. The data source is secondary data obtained from research articles that have been published in national journals. The result of this research is to explain about the 8 components of learning activities in the independent learning curriculum of the independent campus. The conclusion of this research is that learning activities in the independent curriculum of independent campus learning can fulfill the learning needs of the 21st century.  Keywords: independent curriculum for independent learning, learning needs, 21st century  Abstrak: Pembelajaran merupakan upaya untuk membekali siswa dengan materi untuk menunjang kegiatan pembelajaran di kelas. Untuk meningkatkan pembelajaran dengan baik maka. Tujuan dari penelitian ini bahwa adanya kurikulum merdeka belajar kampus merdeka adalah untuk memenuhi kebutuhan pembelajaran di abad 21. Metode yang digunakan dalam penelitian ini adalah metode studi pustaka (library research) yang merupakan penelitian dengan cara menganalisis sumber data. Sumber data yang digunakan adalah data sekunder yang diperoleh dari artikel hasil penelitian yang sudah dipublikasi dalam jurnal nasional. Hasil dari penelitian ini adalah menjelakan tentang 8 komponen kegiatan pembelajaran dalam kurikulum merdeka belajar kampus merdeka. Simpulan penelitian ini bahwa kegiatan pembelajaran dalam kurikulum merdeka belajar kampus merdeka dapat memenuhi kebutuhan pembelajaran abad 21. Kata Kunci: kurikulum merdeka belajar kampus merdeka, kebutuhan pembelajaran, abad 21